PERILAKU PERBERASAN DI JAWA TIMUR - SUDANA, WAYAN; SUDIONO, SUNAR; -, SUJATMO (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 2, No. 2 Juli 2002, 2012)
Rice is the most important and strategic crop. Hence, distribution, price stability of rice and continuous availability at market are the government should achieve the main objectives. This study was conducted at East Java province, the objectives of this study to identify the effectively of floor price policy, factors effecting farm gate price of rice, market structure and efficiency of rice marketing. The results of the study showed that, farm gate price of rice at harvest time (Feb- March) relatively the same with floor price. The main factor effecting of rice price at harvest time is weather, bed weather (heavy rain) price will decrease 20 to 30 percent under floor price. Market structure of rice in East Java is almost competitive and efficiency.
Keywords: Rice, Price and Market structure